Northern Mid-Atlantic Ridge Hydrothermal Habitats: A Systematic Review of Knowledge Status for Environmental Management - Boschen-Rose, Rachel E.; Colaço, Ana (Frontiers in Marine Science, 2021)
Highly specialised biota occurring at hydrothermally active vents on the northern Mid-Atlantic Ridge (nMAR: from south of Iceland to the Equator) have been the subject of numerous research projects over the 36-year period since these habitats were first discovered in the region. When hydrothermal activity ceases, biota endemic to hydrothermally active habitat are lost, and a new biota colonise these sites. Little is known about the biota colonising hydrothermally inactive sulphide habitats on the nMAR, although these sites may be the target of deep-sea mining within the next decade. In this review, we seek to clarify the current knowledge of biological communities colonising hydrothermally active habitats and inactive sulphide habitats on the nMAR. To achieve this, we 1) used a systematic review process to update the species list of benthic invertebrates associated with hydrothermally active habitats, 2) conducted a regional biogeographic analysis of hydrothermally active vent fields on the nMAR, 3) undertook a comprehensive literature review to provide a descriptive account of biological communities, and 4) identified key knowledge gaps in the current understanding of nMAR hydrothermally active and inactive ecosystems. Our updated species list increases the number of benthic invertebrates recorded from hydrothermally active habitat on the nMAR to 158 taxa. Our regional biogeographic analysis separates nMAR hydrothermal vent fields into distinct clusters based on depth/latitude and chimney composition. Vent fields close to the Azores (Menez Gwen, Lucky Strike, Rainbow) formed a separate cluster from those at greater depths south of the Azores (Broken Spur, TAG, Snake Pit, Logatchev, Ashadze-1). Moytirra, located north of the Azores, clustered separately, as did Lost City with its unique carbonate chimneys. We present detailed information on the biological communities at hydrothermally active and inactive habitats in this region, and discuss the information available on the diversity, ecosystem function, trophic relationships, connectivity, temporal variability, and resilience and recovery of these communities. Many knowledge gaps still exist, with detailed information needed on all aspects of the biological communities at hydrothermally active habitat and inactive sulphide habitat on the nMAR to understand and predict impacts from natural and human-induced disturbances in the region.